2.45-GHz wideband harmonic rejection rectenna for wireless power transfer. Issue 5 (10th November 2016) - Kang, Zhanyu; Lin, Xianqi; Tang, Cong; Mei, Peng; Liu, Wangmao; Fan, Yong
Abstract : In this paper, a 2.45-GHz wideband harmonic rejection rectenna for wireless power transfer is proposed. The rectenna comprises a microstrip-fed circular ring slot antenna (CRSA) and a series-parallel rectifier (SPR). A compact micro strip resonant cell is inserted into the CRSA so that the harmonic suppression over a wide bandwidth (3–8 GHz) can be obtained. The radio-frequency (RF)–DC conversion efficiency of the SPR is improved effectively by loading a proper compensating inductance, especially under the low input power levels. Furthermore, the proposed rectenna can easily achieve large-scale rectenna arrays using its simple structure. The adopted rectenna fabricated on a low cost Taconic RF-35 substrate has been measured. By up to 3rd-order harmonic rejection, the efficiency of the rectenna can achieve 70.2% with the optimum load resistance 1 kΩ. Good agreement among the calculated, simulated, and measured rectenna is observed.